The ruling on the liability of the guarantor in the event of the death of the guaranteed in Iraqi jurisprudence and law and its educational impact. - Nassar, Dr. Salim Hamid Nassar; Abdullah, Dr. Firas Majid Abdullah (Sulaimani Journal for Humanities, 2026)
Proposed: The ruling on the guarantee of the apologetic person in the death of the apologetic person, a legal jurisprudential study. Amended: The ruling on the guarantee of the apologetic person in the death of the apologetic person in Iraqi jurisprudence and law and its educational impact. Praise be to God, Lord of the Worlds, and prayers and peace be upon our Master Muhammad, his family, companions, and those who follow them in righteousness until the Day of Judgment. The wisdom of God Almighty required that He not leave His servants without a system that organizes their lives; He legislated a set of rulings, rules, and laws that organize and control people's actions for their Creator and their relationships with each other. These rulings varied between worship, personal status, transactions, and crimes; to achieve the interest of the individual and society, so the limits and retaliation were a worldly punishment to deter people from corruption and committing criminal crimes. They are among the rulings that God legislated to achieve the objectives of Sharia by preserving life, honor, and money. Many crimes and sins that individuals commit and vary over time without a text in them; Because the assessment of penalties for them is left to the guardian under the name of discretionary punishment, the appropriate punishment is imposed on the offender after considering the seriousness of the crime, its circumstances, the extent of its harm to society and individuals, and the condition of the offender; to deter him from repeating his act and to deter others in the future. We wanted to explain in these papers the ruling on the punishment of the punisher by the death of the punished in Islamic law and Iraqi law; due to the importance of this topic and the diversity of crimes in our present time.
Keywords: guarantee; excuse; jurisprudence; effect; death